Household Mobility Dynamics among Young Adults in Established Suburban Council Rental Housing Estates in South African Cities: A Case Study of Kenneth Gardens, Durban - Godfrey Musvoto (Research and Postgraduate Support Directorate, 2021)
The household mobility dynamics of young adults are widely acknowledged as some of the central indicators of residential satisfaction and the quantitative housing deficit. Regardless of this, hardly any studies have been conducted to investigate the trend in South African neighbourhoods. This study investigated the dynamics of household mobility among young adults in the Kenneth Gardens, a subsidised council rental estate in the city of Durban, South Africa. It is based on a survey focusing on household characteristics, profiles of young adults, likely household mobility behaviour of young adults and the factors that influence the mobility of young adults. Descriptive statistical tabulations, analysis of variance (ANOVA) and cross tabulations were used in the analysis. The paper notes that established suburban council rental housing estates are multi-cultural and diverse. Likewise, household formation aspirations and mobility factors among young adults are influenced by ethnic cultural factors and cross-cultural socio-economic factors. The paper argues that the residential satisfaction of young adults and household mobility factors in diverse neighbourhoods should be differentially understood within the context of ethnic and cultural geographies. Furthermore, cross-cultural socio-economic constraints that delay the wishes of young adults to form new households must also be taken into consideration.